A long-term (20 years') follow-up after arthroscopically assisted repair of the TFCC. Issue 5 (3rd September 2017) - Soreide, Endre; Husby, Torstein; Haugstvedt, Jan Ragnar
Abstract: Objective: The present study aimed to assess long-term functional outcome for patients after arthroscopic assisted suture for peripheral tears of the triangular fibrocartilage complex (TFCC). Methods: Eleven patients, 26 (15–59) years old at time of surgery, 48 (35–78) years old at time of follow-up, were available for this 20-year follow-up. Subjective and objective outcomes, such as range of motion, grip strength, patients' satisfaction, pain, and Mayo Modified Wrist Score, were assessed, as well as asking the question if the patients would have had the surgery done again, knowing the outcome, based on a clinical examination and patient reported questionnaires. Results: Median Mayo Wrist score was 85 (30–100) and, according to the Modified Mayo Wrist Score, seven patients presented good or excellent results. The patients reported median low 25 (0–66) on pain and median high 90 (1–100) on satisfaction. Ten patients presented with intact stability of the distal radioulnar joint at follow-up. Compared to the level of pain prior to surgery, two patients reported to be free of pain, five patients experienced major pain relief, two patients reported minor pain relief, while two patients reported no difference. Conclusions: The findings of the present study support the trend of persisting good results for the majority of patients having undergone arthroscopically assisted repair with an outside-in suture technique for peripheral tears of the TFCC.